Perlindungan Hukum Terhadap Pelapor Tindak Pidana Narkotika - M. Zikron; Haryadi Haryadi; Yulia Monita (Fakultas Hukum, Universitas Jambi, 2022)
This study aims to: 1). To find out and analyze, the form of legal protection that can be done for Narcotics Crime Reporters in the Jambi City Region 2). To find out and analyze the obstacles faced in providing legal protection to Narcotics Crime Reporters in the Jambi City Region. The problems discussed are: 1). Forms of Implementation of Legal Protection Against Narcotics Crime Reporters in the City of Jambi ? 2). Obstacles Faced in Providing Protection to Whistleblowers of Narcotics Crimes in the Legal Territory of Jambi City? In this study, the author uses an empirical juridical research method, namely